Effect of urea- and molasses-treated sugarcane bagasse on nutrient composition and in vitro rumen fermentation in dairy cows - Lunsin, Ratchataporn; Duanyai, Suntariporn; Pilajun, Ruangyote; Duanyai, Somporn; Sombatsri, Prapatsorn (Agriculture and Natural Resources, 2018)
The effect of urea- and molasses-treated sugarcane bagasse was studied on the chemical composition, fermentation quality, in vitro gas production and digestibility in dairy cows. The experiment followed a completely randomized design in a 2 x 2 x 2 factorial arrangement of treatments with a control (sugarcane bagasse without any treatment). Factor A was before or after the sugarcane bagasse had been fermented with substrate at 21 d, factor B was the level of urea (0% or 5%), and factor C was the level of molasses (0% or 5%). The results showed that the crude protein content of the sugarcane bagasse increased (p < 0.05) following the urea and molasses treatment, whereas treatment with urea and molasses reduced (p < 0.05) the neutral detergent fiber content and the acid detergent fiber content of the sugarcane bagasse. Moreover, after fermentation, all treatments of the sugarcane bagasse had higher gas kinetics and gas production compared with before fermentation and the control; adding urea and molasses resulted in the highest (p < 0.05) gas production from the soluble fraction (a), from the insoluble fraction (b) and the highest gas potential extent (a+b) as well as cumulative gas production. In addition, in vitro dry matter and organic matter degradability increased (p < 0.05) with the urea and molasses treatments. In conclusion, utilization of 5% urea and 5% molasses as ingredients in sugarcane bagasse treatments would be effective in enhancing the nutritive value and in vitro rumen fermentation. Therefore, sugarcane bagasse treated with urea and molasses could be suitable for use as a roughage source for dairy cattle.